The Brucella suis IbpA heat‐shock chaperone is not required for virulence or for expression of the VirB type IV secretion system VirB8 protein. (8th March 2014) - Berta, P.; Bourg, G.; Hanna, N.; Saadeh, B.; Armengaud, J.; Patey, G.; O'Callaghan, D.
<x xml:space="preserve">Abstract</x> Abstract Brucella suis, facultative intracellular bacterial pathogen of mammals, and Agrobacterium tumefaciens, a plant pathogen, both use a VirB type IV secretion system (T4SS) to translocate effector molecules into host cells. HspL, an α‐crystalline‐type small heat‐shock protein, acts as a chaperone for the Agrobacterium VirB8 protein, an essential component of the VirB system. An Agrobacterium mutant lacking hspL is attenuated due to a misfunctional T4SS. We have investigated whether IbpA (BRA0051), the Brucella HspL homologue, plays a similar role. Unlike HspL, IbpA does not interact with VirB8, and an IbpA mutant shows full virulence and no defect in VirB expression. These data show that the Brucella α‐crystalline‐type small heat‐shock protein IbpA is not required for Brucella virulence. Significance and Impact of Study Many bacteria use type IV secretion systems (T4SS), multi‐protein machines, to translocate DNA and protein substrates across their envelope. Understanding how T4SS function is important as they play major roles in the spread of plasmids carrying antibiotic resistance and in pathogenicity. In the plant pathogen Agrobacterium tumefaciens, HspL, an α‐crystalline‐type small heat‐shock protein, acts as a chaperone for the essential type IV secretion system component VirB8. Here, we show that this is not the case for all T4SS; in the zoonotic pathogen Brucella suis, IbpA, the protein most related to HspL, does not play this role.